2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0374.r1
|View full text |Cite
|
Sign up to set email alerts
|

Indications for a single-stage exchange arthroplasty for chronic prosthetic joint infection

Abstract: Aims Prosthetic joint infections (PJIs) of the hip and knee are associated with significant morbidity and socioeconomic burden. We undertook a systematic review of the current literature with the aim of proposing criteria for the selection of patients for a single-stage exchange arthroplasty in the management of a PJI. Material and Methods A comprehensive review of the current literature was performed using the OVID-MEDLINE, EMBASE, and Cochrane Library databases and the search terms: infection and knee arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 43 publications
0
51
0
9
Order By: Relevance
“…In most cases, GRA is part of two-stage revision arthroplasty in the treatment of PJI. However, single-stage revision has become more popular in recent years to treat PJI 8. The Girdlestone situation could result in a permanent clinical situation when 1) bone quality or soft tissue coverage is not strong enough to insert a new prosthesis, 2) the infection cannot be controlled, or 3) patients are unfit for surgery due to e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, GRA is part of two-stage revision arthroplasty in the treatment of PJI. However, single-stage revision has become more popular in recent years to treat PJI 8. The Girdlestone situation could result in a permanent clinical situation when 1) bone quality or soft tissue coverage is not strong enough to insert a new prosthesis, 2) the infection cannot be controlled, or 3) patients are unfit for surgery due to e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the available literature has shown dismal rates in the management of MRSA-PJIs, with some studies understandably including the presence of MRSA as a contraindication to performing single-exchange surgery [15, 26, 32, 33]. However, the high infection-free rate of 93.1% achieved in this case-series gives us a positive outlook that MRSA-PJIs can be satisfactorily managed with predictable outcomes, even by single-stage exchange surgery providing current infectious agents eradication strategies.…”
Section: Discussionmentioning
confidence: 84%
“…Patient selection must be considered when determining the treatment strategy for prosthetic joint infections. Thakrar et al concluded that a one-stage exchange is an acceptable form of surgical treatment in patients without severe immunocompromise, significant soft-tissue or bony compromise, or concurrent acute sepsis [13]. Another study reported that the absence of wound complications after the initial total hip replacement, good general health of the patient, infecting organism of methicillin-sensitive Staphylococcus epidermidis, Staphylococcus aureus, or Streptococcus species, and an organism sensitive to the antibiotic mixed into the bone cement were factors associated with a successful one-stage exchange THA [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, reported failure rates after a two-stage hip revision range from 5 to 18% [11,12]. Thus, there has been debate whether a one-stage exchange or two-stage exchange offers the correct treatment [13]. One-stage exchange arthroplasty has particularly gained interest due to less morbidity, mortality, and functional impairment [14].…”
Section: Introductionmentioning
confidence: 99%